The Contradictions of Free Market System and The Impacts of FDI and Foreign Trade on Economy - Hasan Alpagu (Turkish Economic Review, 2014)
This paper examines the effects of the FDI and foreign trade (Exports and Imports) as well as their importance in international economic activities. A central subject the study is to examine the impact of FDI and foreign trade on the growth and prosperity status of countries. Whereby the paper examines the role of international business on the developing progress of countries. The economic growth of a country depends on the quantity and productivity of the economic factors. For that reason FDI and Import-Export are most significant economic activities, which have substantial effects on the quantity as well as quality of economic factors in any country. On the other side, customs union, quotas and regional trade pacts deactivate partly or in some cases even completely the projected effects of Smith's absolute and Ricardo's comparative advantages theories in the international production cooperation. The study examines this situation from a modern economic point of view.
Keywords: F10; 330; FDI; Export; Import; Capitalist System; Less Developed Countries; Invisible Hand